DETERMINAN TINGKAT PENGANGGURAN TERBUKA DI INDONESIA - Pamungkas, Bayu Dalang; Kartika, Metasari (Jurnal Ekonomi Integra, 2025)
The phenomenon of open unemployment in Indonesia is an important issue that needs serious attention, especially when the economy is growing steadily. While economic growth should create more jobs, there are challenges such as a mismatch between the education graduates receive and the needs of the job market, as well as more investment going into sectors that do not absorb much labor. This study aims to understand the factors that influence the unemployment rate in Indonesia, by looking at the influence of economic factors such as economic growth, the number of college graduates, investment, population growth, and minimum wage. Using data from 2017 to 2023 across 34 provinces and the panel data analysis method, this study finds that economic growth and population growth have a significant effect on unemployment, while the number of college graduates, investment, and minimum wage show no significant effect. The findings suggest the importance of creating equitable economic growth and improving the matching of education with labor market needs.